RASA KEPEMILIKAN: PENERAPAN KONSEP 'HOME' DI PANTI ASUHAN - Pratama, Muhammad Bayu; Ginting, Salmina Wati (Universitas Medan Area, 2024)
Orphanages are responsible child protection institutions that safeguard children's rights and act as substitutes for parents. The problem lies in the proliferation of illegal and unfit orphanages. This study investigates various strategies and approaches used in providing inclusive caregiving environments aimed at creating a place where children feel comfortable. By examining the implementation of the